PENGARUH BRAND IDENTIFICATION, SELF IMAGE EXPRESSION, SENSE OF NATURAL, LAYOUT POSITIVELY, BRAND PASSION, BRAND LOVE, BRAND PRIDE TERHADAP BRAND LOYALTY RICHEESEE FACTORY - Trenvaldo Gunawan; Margaretha Pink Berlianto (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2023)
This study aims to determine the effect of brand identification on brand passion and brand love, effect of brand identification on brand pride and brand loyalty, effect of self-image expression on brand passion and brand love, effect of self-image expression on brand pride and brand loyalty, effect of sense of natural environment on brand passion and brand love,  brand pride, also brand loyalty, effect of Layout on brand passion and  brand love,   brand pride, also brand loyalty, influence of brand passion, brand love and brand pride towards brand loyalty. The sample is 239 consumers who have purchased at Richeese Factory at least 3 times and the analysis technique uses Smart PLS. Based on the results of the analysis, it can be concluded that Brand Identification has no effect on brand passion, brand identification has a positive effect on brand love and brand pride, also on brand loyalty, self-image expression has a positive effect on brand passion and brand love, self-image expression has a positive effect on brand pride and brand loyalty, also brand passion and brand love layout positively has no effect on brand passion and brand pride, layout positively has a positive effect on brand love and brand loyalty,  brand love has a positive effect on brand loyalty, meanwhile brand pride has no effect on brand loyalty.